Inpatient preferences among patients with multiple chronic conditions in China: A discrete choice experiment - Yueqin Wang; Shiyin Wu; Yuehua Chen; Ling Xiao; Qingling Su; Xiaoyin Huang; Weikang Wang; Wanxin Li; Shanshan Du; Wenbin Liu; Weimin Ye (BMC Primary Care)
Abstract Background Multiple chronic conditions (MCC) have become a leading cause of low vitality and high mortality among the Chinese population. Although a series of policies has been implemented to promote patients’ rational access to health care, patients still prefer a higher level of inpatient service, hampering the efficient utilization of resources in county hospitals, which are the first point of contact for inpatient care. Thus, this study aimed to identify the factors that affect MCC patients’ inpatient preferences and the extent to which these factors influence their decisions, thereby guiding inpatient service utilization among MCC patients. Methods Five attributes (institution scale, waiting time for hospital admission, presence of acquaintances, travel time from residence to hospital, and out-of-pocket expenses per visit) were identified to estimate inpatient choice for MCC patients through a discrete choice experiment. A partial factor analysis was performed to generate selection sets. Data were collected from MCC patients aged between 35 and 75 years, in Fuqing City, China. A mixed logit model was used to analyse MCC patients’ preferences for each attribute. Willingness to pay was estimated by regression coefficients, and interaction terms were included in the model to estimate the heterogeneity of inpatient preferences among MCC patients. Results A total of 504 valid questionnaires were included in the analysis. The most important attribute of patients when choosing inpatient care is out-of-pocket expenses per visit, followed by travel time from residence to hospital, waiting time for hospital admission, institution scale, and presence of acquaintances. In addition, patients were willing to pay ¥1253, ¥434, and ¥323 for shorter times from the residence to the hospital, larger institutional scale, and beds available on the day, respectively. The findings of the interaction analysis indicated that age and gender also influence MCC patients’ inpatient preferences. Conclusion This study provides evidence of the inpatient preferences of MCC patients. Increasing inpatient insurance reimbursement rates, bolstering the leading role of district and county hospitals in the area, and strengthening information systems will empower district and county hospitals to effectively serve as the first point of contact for inpatient care.